Étude du régime alimentaire de deux espèces de Cichlidae en situation contrastée dans un estuaire tropical inverse d'Afrique de l'Ouest (Casamance, Sénégal) Title: Study of the diet of two species of Cichlidae in contrasting situation in a West African (Casamance, Senegal) inverse tropical estuary - (:unkn) unknown (My University, 2011)
The dam anti-salt of Maka was set up as 1998 on the river Casamance (Senegal) to restore the fresh water conditions for the benefit of the rice production activity of the local populations. It separates two environments of salinity contrasted: a downstream salted part under influence of the inverse estuary and an upstream part of fresh water. The comparative study of the diets of two Cichlidae Sarotherodon melanotheron heudelotii and Tilapia guineensis living on both sides on the anti-salt dam of Maka was made on the basis of samplings over three different periods in 2006 and 2007: a warm wet season (in October), a cold dry season (in February) and a warm dry season (in May). The diets of both species are approached by a classic method of analysis of the stomach contents by noting the occurrences of preys. Compared with the Ndour et al. (2011) J. Sci. Halieut. Aquat., 4: 120-133 121 populations of S. m. heudelotii and of T. guineensis who live upstream to the dam, those living downstream to the dam present more important occurrences of preys. S. m. heudelotii tends to ingest of advantage of plant fragments to the detriment of the mud when the salinity becomes high. On the other hand, T. guineensis who has a wider trophic spectrum, tends to consume more vase (bivalves) than of plant fragments, when the salinity increases. The comparison of the diets of this two Cichlidae on both sides of the dam, shows an evolution of their diets according to the environmental conditions.
Keywords: African Research